2016
DOI: 10.1155/2016/8789624
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Epidemiology of Poisoning in the East African Region: A Literature Review

Abstract: The establishment and strengthening of poisons centres was identified as a regional priority at the first African regional meeting on the Strategic Approach to International Chemicals Management (SAICM) in June 2006. At this meeting, the possibility of a subregional poisons centre, that is, a centre in one country serving multiple countries, was suggested. The WHO Headquarters following consultation with counterparts at the WHO Regional Office for Africa (AFRO) and the SAICM Africa Regional Focal Point success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
1
15
1
1
Order By: Relevance
“…In that study, Gesesew et al indicated that the probability of pesticide exposure was very high, and the two most important routes of exposure as reported by farmers were inhalation and ingestion [ 17 , 18 ]. The most perceived human health concerns were skin irritation, deaths, and respiratory and eye problems, which were also reported in other investigations [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Although people interviewed in our study did not name asthma as a pesticide health problem, 24% of farmers in the study in Ethiopia [ 17 ] cited asthma as a serious health problem.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In that study, Gesesew et al indicated that the probability of pesticide exposure was very high, and the two most important routes of exposure as reported by farmers were inhalation and ingestion [ 17 , 18 ]. The most perceived human health concerns were skin irritation, deaths, and respiratory and eye problems, which were also reported in other investigations [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Although people interviewed in our study did not name asthma as a pesticide health problem, 24% of farmers in the study in Ethiopia [ 17 ] cited asthma as a serious health problem.…”
Section: Discussionsupporting
confidence: 78%
“…In an opinion article, some evidence has been gathered to suggest the serious risk of asthma among farmers exposed to high levels of pesticides [ 20 ]. Acute pesticide poisoning of farmers and relatives occurs mostly via inhalation [ 2 ], while risks of long-term effects may occur through ingestion of pesticide residues in foods [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Once in the human body, pesticides can, via different biochemical pathways, lead to chronic diseases such as cancer, diabetes, birth defects, chronic obstructive pulmonary disease and reproductive disorders [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suspected methanol poisoning outbreaks with fatal outcomes have been reported in Uganda [9]. However, no thorough investigations were conducted during those outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately high amounts of these hazardous chemicals are allowed in the food chain at the expense of everyone's health. A literature review on pattern and epidemiology of poisoning in East African region reported organphosphorus poisoning as one of the key causes of nontraumatic coma in Zambia (Tagwireyi et al 2016).…”
Section: Discussionmentioning
confidence: 99%